PENDIDIKAN ISLAM DALAM PEMBINAAN AKHLAKUL KARIMAH ANAK : (Studi Pada Pesantren Dengan Lembaga Formal Dan Non-Formal) - Moh. Sholihuddin (Atthiflah: Journal of Early Childhood Islamic Education, 2022)
There are three forms of educational institutions that develop in our country today, namely formal, non-formal and informal. A formal educational institution is an educational institution whose curriculum is created and managed by the government from the paud level to the college level. Then non-formal educational institutions are educational institutions whose curriculum is created and managed by the community which includes pesantren or dayah educational institutions. While informal education is education built or organized by families and the environment is only limited to education without being educated and does not require permission from the government. This article discusses Islamic education in the development of children's morals karimah in formal education and non-formal education. The method used in writing this article is the result of observation of formal and non-formal educational institutions in Lasem Rembang Regency. As a result, there are educational institutions or foundations that manage both (formal schools and boarding schools) there are also only boarding schools without any formal schools. In the development of morals in the formal institution of the teacher is the main person in charge other than as an educator teachers have responsibility for the development of student morals. In this institution, the level of discipline of students is higher, while in pesantren boarding schools the level of student piety is higher